Study on Phytochemical Profiling of Euphorbia cyathophora Leaf Extracts and Their Potential Antimicrobial, Larvicidal, and Pupicidal Properties Against Earias vittella: Life Sciences-Zoology - Moorthi, Kannan; Natesan, Kanagaraju; Balamurugan, Chandramohan; Pari, Madhiyazhagan (International Journal of Life Science and Pharma Research, 2023)
Earias vittella is a serious polyphagous agricultural pest that can directly or indirectly damage crops and stored products worldwide. Using synthetic chemicals in pest control has resulted in physiological resistance and adverse environmental effects. However, this alternative to plant-based pest control systems is ecologically friendly and biodegradable. Moreover, Euphorbia cyathophora is a medicinal plant used for many therapeutic activities. Therefore, the present study is aimed at E. cyathophora leaf extract evaluation of the phytochemical, in vitro antimicrobial, larvicidal, and pupal activity of E. vittella. A preliminary phytochemical screening of E. cyathophora leaf extracts revealed numerous bioactive components such as alkaloids, flavonoids, sterols, terpenoids, anthraquinones, carbohydrates, and essential oils. GC-MS analysis of E. cyathophora leaf different extracts revealed the presence of 29 phytochemicals. Among the extracts tested, the methanolic leaf extract showed the highest range of growth inhibition against gram-positive bacteria Streptococcus iniae (15 ± 0.26) and gram-negative bacteria Aeromonas hydrophila (13 ± 0.6), while antifungal activity against Aspergillus flavus (14 ± 0.2) and Aspergillus niger (12 ± 0.36) compared to other solvent extracts. In addition, the bioefficacy of E.Cyathophora leaf extract treated against IV instar larvae and pupae of E. vittella; however, the highest larval and pupal mortality was observed in the methanol extract at 750 ppm, followed by acetone and chloroform against E. vittella. Larvicidal activity of E. cyathophora leaf extracts showed LC50 and LC90 values: methanol 298.64 ppm (708.14); Acetone 362.61 ppm (848.56), and chloroform 415.18 ppm (937.31), respectively. Similarly, thepupicidal effect of E. Cyathophora leaf extracts showed LC50 and LC90 values: methanol 470.25 ppm (958.01); acetone 527.36 ppm (996.35) and chloroform 545.55 ppm (997.88). This study strongly suggests that E. cyathophora leaf extract exhibited significant larval and pupal mortality and potential antimicrobial activity, which can be observed as the development of a new botanical preparation for economic pest control.